Clinical Outcome of Autologous Cultivated Oral Mucosal Epithelial Transplantation in Ocular Surface Reconstruction. Issue 10 (October 2019) - Gopakumar, Vidya; Agarwal, Shweta; Srinivasan, Bhaskar; Krishnakumar, Subramanian; Krishnan, Uma Maheswari; Iyer, Geetha
Abstract : Purpose: To evaluate the outcomes of autologous cultivated oral mucosal epithelial transplantation (COMET) in ocular surface reconstructive procedures. Methods: Twenty-five eyes of 24 patients who underwent COMET for ocular surface reconstruction were studied retrospectively from April 2011 to March 2014. Oral mucosal biopsy of 2 mm 2 was harvested from all patients and cultured on amniotic membrane for 14 days. COMET was performed as a means to achieve corneal epithelization (group 1) and for fornix reconstruction (group 2). The extent of epithelization achieved (group 1) and the depth of the fornix reconstructed (group 2) were the primary outcome measures. Results: Six eyes of 5 patients [2 chemical injury (CI), 3 Stevens–Johnson Syndrome (SJS)] underwent COMET for nonhealing of an epithelial defect within a month after insult or had a nonhealing defect since insult despite maximal medical/surgical therapy. Group 2 included 19 eyes of 19 patients (10 CI, 8 SJS, 1 ocular cicatricial pemphigoid) which underwent COMET for fornix reconstruction. Postsurgery, the cornea was fully epithelized in 66.67% of the eyes (n = 4) and partially epithelized in 33.33% of the eyes (n = 2). The overall improvement in surface epithelization was statistically significant ( P = 0.046). Reconstruction of an anatomically deep fornix was achieved in 57% of the eyes (4 CI, 6 SJS and 1 ocular cicatricial pemphigoid). The fornix was partially formed in 26% of the eyes (4 CI and 1 SJS). The overall improvement in fornix reconstruction was considered statistically significant ( P = 0.024). The follow-up ranged from 1 to 5 to 27 months with a mean follow-up of 18 months SD ±8.9. Conclusions: COMET, by providing an alternate source of epithelium, aids in faster epithelization and thus can be considered as an option in management of severe grade CI or SJS in the acute stage as well as in fornix reconstructive procedures in chronic stage of ocular surface disorders.